Contractor’s Performance Appraisal System in the Malaysian Construction Industry: Current Practice, Perception and Understanding - Zahreen Mohd Arof, Khairul; Ismail, Syuhaida; Latif Saleh, Abd (International Journal of Engineering and Technology, 2018)
Performance appraisal system is a common practice in any organisation to appraise performance of workers. In the Malaysian construction industry, performance appraisal system is applied to appraise contractor’s performance in many angles including: quality performance; time performance; cost performance; environmental performance; health and safety performance; productivity performance; and human resources performance. This is where the Construction Industry Development Board (CIDB) established three guidelines in strengthening the Construction Industry Transformation Programme (CITP) by appraising the contractor’s performance through identification of their weaknesses as well as drafting and offering suitable trainings in enhancing their performance. This paper is therefore undertaken with the objectives of: (1) determining the current practice of contractor’s performance appraisal system in the Malaysian construction industry; and (2) examining the construction players’ perception and understanding on the existing contractor’s performance appraisal system in the Malaysian construction industry. A set of questionnaires is designed and distributed to 157 contractors from G1 to G7 class. The paper finds that: (1) contractor’s performance appraisal system is benefiting the contractors yet should be improved for its efficiency; and (2) construction players have sufficient understanding on contractor’s performance appraisal system. It is expected that the improvement of contractor’s performance appraisal system via the findings of this paper would assist in achieving the three focuses of Transformasi Nasional 2050 (TN50), namely science and technology, urban prosperity as well as environment.